Faktor Penolakan Berulang Dalam Hubungan Biologis Sebagai Penyebab Perceraian Analisis Putusan Di Pengadilan Agama Medan (2021-2023) - Muhyiddin, Mhd. Ibnu Imam; Imam Yazid (Lex Stricta : Jurnal Ilmu Hukum, 2025)
Divorce is a social phenomenon that continues to increase, including in the Medan Religious Court, with multidimensional causes. One influential factor that is often overlooked is the quality of biological relationships (emotional support) within the household. This study aims to analyse the influence of biological relationships on divorce, identify the forms of biological problems in divorce cases, and explore the perceptions of judicial officials on divorce cases at the Medan Religious Court during the period 2021-2023. The method used is a legal-empirical study with a descriptive-analytical approach through document analysis of 130 divorce cases and interviews with judges and court clerks. The results of the study show that 22.3% of divorce cases are related to biological problems, either explicitly or implicitly, mainly in the form of lack of intimacy, refusal of sexual relations, and sexual dysfunction. These problems trigger domestic conflicts and contribute significantly to divorce. These findings emphasise the importance of biological relations in maintaining the integrity of the household in accordance with Islamic law and legislation. Therefore, it is necessary to strengthen premarital education, family counselling, and judicial mediation that take into account biological needs as a means of preventing divorce.